2010
DOI: 10.1039/c0lc00019a
|View full text |Cite
|
Sign up to set email alerts
|

Reagent-release capillary array-isoelectric focusing device as a rapid screening device for IEF condition optimization

Abstract: This report describes the fabrication and characterization of a simple and disposable capillary isoelectric focusing (cIEF) device containing a reagent-release capillary (RRC) array and poly(dimethylsiloxane) (PDMS) platform, which allows rapid (within 10 min) screening of cIEF conditions by introducing a sample solution into plural RRCs by capillary action followed by electric field application. To prepare the RRC, covalent immobilization of poly(dimethylacrylamide) (PDMA) was conducted to suppress electro-os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…11). 50 A second application was for the combination of ELISA-cIEF by synthesizing a new fluorescent dye that reacts with the alkaline phosphatase-labeled antibody to produce an organic fluorescent molecule with pI. In this case, the final enzymatic reaction products of capillary ELISA are concentrated by IEF to give highly sensitive signals for proteins.…”
Section: ·2 Microchip Capillary Electrophoresismentioning
confidence: 99%
“…11). 50 A second application was for the combination of ELISA-cIEF by synthesizing a new fluorescent dye that reacts with the alkaline phosphatase-labeled antibody to produce an organic fluorescent molecule with pI. In this case, the final enzymatic reaction products of capillary ELISA are concentrated by IEF to give highly sensitive signals for proteins.…”
Section: ·2 Microchip Capillary Electrophoresismentioning
confidence: 99%
“…As model cases, solutions and hydrogels containing 10 -4 M sulforhodamine B (anionic fluorescent dye) were prepared with deionized water and acrylamide monomer solution, respectively. To prevent the electroosmotic flow during the electrokinetic injection, the inner surface of the capillary was modified with poly-(dimethylacrylamide) (PDMA) using the same procedure as reported previously [24]. Both ends of the PDMA-coated capillary filled with a buffer solution were in contact with the solutions or hydrogels.…”
Section: Estimation Of the Electrophoretic Migration Of Ions From Thementioning
confidence: 99%
“…Yang et al [20,21] and Zhu et al [22,23] reported the immobilization of carrier ampholytes (CAs) on a monolithic column in the microchannel, thereby avoiding the addition of carrier ampholytes into the sample solution to prevent current increase. In our previous study, we reported that the use of a "reagent-release capillary" (RRC) facilitated the MIEF procedure simply by introducing a sample solution into a capillary via capillary action, soaking the cathodic and anodic ends of the capillary into basic and acid solutions filled in reservoirs, respectively, and applying an electric field [24,25]. However, this technique still requires a step of manual application of the acid and base solutions to the reservoirs after sample introduction into the RRC.…”
Section: Introductionmentioning
confidence: 99%
“…To suppress both the fast electroosmotic flow and nonspecific adsorption of proteins, the inner surface of the capillary was modified with polyDMA (PDMA) as previously reported. 31 The reagents for both the enzyme activity assay and CIEF experiments were physically adsorbed onto the surface of the PDMA layer as a thin soluble coating. Typically, a solution containing 0.3% (v/v) Bio-Lyte 3/10, 0.1% (w/v) Tween 20, 0.7% (w/v) glycerol, and 1.0 × 10 -5 M R110-based substrate for trypsin activity assay was introduced into the PDMA-coated square capillary (5.0 cm in length).…”
Section: Preparation Of the Rrcsmentioning
confidence: 99%
“…30 In addition, RRCs containing CAs was also developed and combined with CIEF to perform the focusing and separation of proteins with a simple experimental procedure. 31 In this study, we propose to use the fluorescent enzyme substrate, rhodamine 110 (R110) diamide and RRC-IEF for a simple, sensitive, and rapid enzyme activity assay with the consumption of small amounts of samples and reagents. In the R110-based substrate, two amide groups are cleaved and substituted with amino groups by proteases.…”
mentioning
confidence: 99%